Understanding the ionic activity and conductivity value differences between random copolymer electrolytes and block copolymer electrolytes of the same chemistry. Issue 25 (22nd April 2021) - Ramos-Garcés, Mario V.; Li, Ke; Lei, Qi; Bhattacharya, Deepra; Kole, Subarna; Zhang, Qingteng; Strzalka, Joseph; Angelopoulou, Polyxeni P.; Sakellariou, Georgios; Kumar, Revati; Arges, Christopher G.
Abstract : Random copolymer electrolytes have better permselectivity but lower ionic conductivity than block copolymer electrolytes of the same repeat unit chemistry. Abstract : Herein, a systematic study where the macromolecular architectures of poly(styrene- block -2-vinyl pyridine) block copolymer electrolytes (BCE) are varied and their activity coefficients and ionic conductivities are compared and rationalized versus a random copolymer electrolyte (RCE) of the same repeat unit chemistry. By performing quartz crystal microbalance, ion-sorption, and ionic conductivity measurements of the thin film copolymer electrolytes, it is found that the RCE has higher ionic activity coefficients. This observation is ascribed to the fact that the ionic groups in the RCE are more spaced out, reducing the overall chain charge density. However, the ionic conductivity of the BCE is 50% higher and 17% higher after the conductivity is normalized by their ion exchange capacity values on a volumetric basis. This is attributed to the presence of percolated pathways in the BCE. To complement the experimental findings, molecular dynamics (MD) simulations showed that the BCE has larger water cluster sizes, rotational dynamics, and diffusion coefficients, which are contributing factors to the higher ionic conductivity of the BCE variant. The findings herein motivate the design of new polymer electrolyte chemistries that exploit the advantages of both RCEs and BCEs.